Isoselenazole Synthesis by Rh-Catalyzed Direct Annulation of Benzimidates with Sodium Selenite - Xu-Xu, Qing-Feng; Nishii, Yuji; Miura, Masahiro (Chemistry an international journal, 2023)
Organoselenium compounds have attracted significant research interest because of their potent therapeutic activities and indispensable applications in the organic chemistry field. The selenation reactions conventionally rely on the use of sensitive Se reagents; thus, new synthetic methods with improved efficiency and operational simplicity have recently been of particular interest. In this manuscript, we report a Rh-catalyzed direct selenium annulation using tractable sodium selenite (Na2SeO3) as the limiting reagent. The selenite species was converted to highly electrophilic SeO(OBz)2 in situ upon treatment with Bz2O, thereby undergoing C–H/N–H double nucleophilic selenation. A series of benzimidates successfully underwent selenation under mild reaction conditions to afford isoselenazole derivatives.